Faktor - Faktor Yang Berhubungan Dengan Kepatuhan Perawat Rawat Inap Dalam Pelaksanaan Five Moments dan Hand Hygiene - Dian Matsyiwati Putri Sari; Ahmad Rizal; Sancka Stella G. Sihura (Inovasi Kesehatan Global, 2024)
. Introduction: Nurses have a high risk of transmitting pathogens through their hands, because nurses spend the longest time with patients. Apart from this, a nurse must be able to comply with predetermined nursing duties and ethics, including "hand hygiene five moments" which is the term used for washing hands. Objective: To determine the factors related to inpatient nurses' compliance with implementing the five moments and hand hygiene at AZRA Bogor Hospital. Method: This type of research is quantitative with the method used, namely a cross-sectional design with a population of nurses who are still actively working at AZRA Bogor Hospital with a sample size of 87 respondents. Data collection techniques use observation sheets and questionnaires with several closed questions. Data analysis in this study used the chi square test. Results: The highest age of inpatient nurses was 64.4% at the age of 26 -35 years at AZRA Bogor Hospital, Diploma III (D3) education was 59.8%, PK 3 career level was 36.8%, good knowledge was 63.2%, compliance was 59.8%. Variables related to factors related to inpatient nurse compliance are age and education. Variables that have no relationship are career level and knowledge. Conclusion: Implementation of five moments and hand hygiene in hospitals to prevent transmission of HAIs to patients, visitors and health workers.